School geography in front of religious intolerance: challenges and proposals - Rocha, Marcos da Silva (Geosaberes; Vol 9 No 18 (2018): May - Aug., 2018)
Conflicts involving religion have become increasingly visible in the international discussion agenda. Several tragic events are constantly motivated, too, for reasons of religious intolerance. There is no denying the relevance of the religious factor to the identity of the nation and the individual, so it is essential to debate to what extent dogmatism and religious fundamentalism are hurting human dignity. The focus of this article is to score the results of the debate on religious intolerance in a secondary school by understanding the student as a religious person (or not) living in a neighborhood where there will also be cases of religious intolerance. It also discusses the guidelines proposed by the school on the subject. Finally, a reflexive and mediated activity is proposed to serve as a basis for discussions and practices of religious tolerance.
Keywords: Geografia Escolar; Religião; Educação; Ensino Médio